2005
DOI: 10.1002/anie.200501914
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Hollow‐Fiber Membranes for the Production of Oxygen‐Enriched Air

Abstract: Mixed‐ion and electron‐conducting perovskite membranes are used to produce oxygen‐enriched air (see picture). These membranes are thermally and mechanically stable at high temperatures (>875 °C) over a long period of time, thus making them suitable for industrial processes. Oxygen concentrations of the enriched air typically reach 30–50 vol %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(60 citation statements)
references
References 20 publications
0
56
0
4
Order By: Relevance
“…Current tonnage O 2 production by cryogenic processes is very energy expensive and production cost reduction by 35% or more is required [1][2][3][4], which in turn is driving academic and industrial researchers toward membrane technology development for the last decade. Of particular attention, ion conducting ceramic membranes have attracted the attention of the research community, with over 20 laboratories worldwide conducting research on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Current tonnage O 2 production by cryogenic processes is very energy expensive and production cost reduction by 35% or more is required [1][2][3][4], which in turn is driving academic and industrial researchers toward membrane technology development for the last decade. Of particular attention, ion conducting ceramic membranes have attracted the attention of the research community, with over 20 laboratories worldwide conducting research on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its ability to support very thin walled membranes, the hollow fiber geometry also maximizes the surface area per unit volume. Recent developments show large improvements in oxygen permeation rates in hollow fibers 1,12,13,15,17,18 compared with flat, self-supported membranes. Similar results might be compared with some of the best results in the literature on flat supported membranes.…”
Section: Supported Miec Membranesmentioning
confidence: 99%
“…Hollow fiber membranes can be fabricated using simple processing steps, without the use of porous substrate. Perovskite capillaries with an outer diameter from 0.5 to 3 mm and wall thicknesses from 50 to 500 µm have been manufactured 12,13 . However, material measurements.…”
Section: Supported Miec Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that the oxygen-enriched air can be produced by pressuring the feed air through the OPMs to another air side with lower pressure (Fig. 9) [120]. For example, an oxygen-enriched air with the oxygen content of 40-50% can be produced to satisfy the demand of ammonia production.…”
Section: Production Of O 2 -Enriched Airmentioning
confidence: 99%